PEMBUKTIAN TINDAK PIDANA ASAL DALAM PERKARA TINDAK PIDANA PENCUCIAN UANG BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Farahwati Farahwati (Universitas 17 Agustus 1945 Samarinda, 2022)
Criminal cases related to assets or assets resulting from crime are known as money laundering crimes. The money laundering case is not only a threat to the stability and integrity of the economy and the state financial system, but also endangers the lives of the people, the nation and the State of Indonesia. In its development, money laundering offenses cases are increasingly widespread and complex to various sectors. The problem in this paper is whether the criminal act of Money Laundering must first be proven the crime of origin, and what are the legal evidence in the Law on the Prevention and Eradication of the Crime of Money Laundering. There is a close relationship between the crime of money laundering and the crime of origin. These problems arise in the prosecution process related to whether both must be proven or is it sufficient to prove the crime of money laundering without first proving the original crime. The reason is, in the regulation regarding the prosecution of money laundering cases, namely Article 69 of Law No. 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering stipulates that in conducting investigations, prosecutions and examinations in courts of cases of Money Laundering, it is not obligatory to first prove the original crime.The normative juridical writing method uses primary and secondary legal materials with qualitative juridical analysis. Analysis of the effectiveness of handling the crime of money laundering without prior proof of the predicate crime, in terms of handling the crime of money laundering without the obligation to prove the predicate crime can be said to be effective because it can facilitate the judicial process. In the crime of money laundering, it still provides an opportunity to prove that the assets obtained are assets resulting from legitimate activities.